2014
DOI: 10.1259/bjr.20140081
|View full text |Cite
|
Sign up to set email alerts
|

Exploring silver as a contrast agent for contrast-enhanced dual-energy X-ray breast imaging

Abstract: Cite this article as: Karunamuni R, Tsourkas A, Maidment ADA. Exploring silver as a contrast agent for contrast-enhanced dual-energy X-ray breast imaging. Br J Radiol 2014;87:20140081. FULL PAPER Exploring silver as a contrast agent for contrast-enhanced dual-energy X-ray breast imaging Objective: Through prior monoenergetic modelling, we have identified silver as a potential alternative to iodine in dual-energy (DE) X-ray breast imaging. The purpose of this study was to compare the performance of silver a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 37 publications
0
43
0
Order By: Relevance
“…3,4 While all soft tissues have similar ratios of attenuation between the low and high energy x-ray images, the contrast agents used have higher attenuation in the high energy window, due to their k-edge. 8 A logarithmically weighted image subtraction is done to create a DE image. The signal from the breast tissue is suppressed and that from the contrast agent is enhanced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 While all soft tissues have similar ratios of attenuation between the low and high energy x-ray images, the contrast agents used have higher attenuation in the high energy window, due to their k-edge. 8 A logarithmically weighted image subtraction is done to create a DE image. The signal from the breast tissue is suppressed and that from the contrast agent is enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…8 It has been shown via experiments that silver nanoparticles produce 40% more contrast than iodine in DEM phantom imaging. 8 Proof of concept imaging was done in mice with silica-coated silver nanoparticles. The results confirmed that silver nanoparticles produce strong DEM contrast in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…A weighting factor, W , was applied to the LE image in order to remove the background structures (bone, soft tissue) in the DE image. W was calculated to be analogous to previous formulations [14], using the average signal intensities ( SI ) of the bone and soft tissue regions: W=lnfalse(SIbHEfalse)lnfalse(SIsHEfalse)lnfalse(SIbLEfalse)lnfalse(SIsLEfalse). …”
Section: Methodsmentioning
confidence: 99%
“…Silver (Ag) has been identified as a new candidate agent for DE mammography that can provide more contrast than iodine at clinically utilized imaging parameters [1416]. The lower k-edge energy of silver (25.5 keV) provides two key benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation